Effect of Fertilising Chicory (Cichorium intybus L.) in the Second Vegetation Year - Nicoleta Moraru; Neculai Dragomir; Ioan Pădeanu; Anca Sala; Dorin Camen; Dorin Rechiţean; Claudiu Ghiocel; Voichiţa Gherasim (Scientific Papers Animal Science and Biotechnologies, 2023)
In the conditions of the Banat’s Plain (Romania), chicory can be an important fodder crop well adapted to the climate conditions in the area. Research results show that this species is positively influenced by the use of chemical or organic fertilisers. Applying nitrogen fertilisers on a yearly basis at rates of N50-100 lead, in the second vegetation year, to productions higher with 22-34% than in the control variant (no fertilisation). The remnant effect of animal manure was obvious in the second year of application too, when we obtained, at a rate of 40 t/ha, an increase of 26% compared to the control variant.